Alternative Therapy of Psychosis: Potential Phytochemicals and Drug Targets in the Management of Schizophrenia - Ammara Saleem; Qurat-; Qurat-; Muhammad Furqan Akhtar (Frontiers Media S.A., 2022)
Schizophrenia is a chronic mental and behavioral disorder characterized by clusters of symptoms including hallucinations, delusions, disorganized thoughts and social withdrawal. It is mainly contributed by defects in dopamine, glutamate, cholinergic and serotonergic pathways, genetic and environmental factors, prenatal infections, oxidative stress, immune system activation and inflammation. Management of schizophrenia is usually carried out with typical and atypical antipsychotics, but it yields modest benefits with a diversity of side effects. Therefore, the current study was designed to determine the phytochemicals as new drug candidates for treatment and management of schizophrenia. These phytochemicals alter and affect neurotransmission, cell signaling pathways, endocannabinoid receptors, neuro-inflammation, activation of immune system and status of oxidative stress. Phytochemicals exhibiting anti-schizophrenic activity are mostly flavonoids, polyphenols, alkaloids, terpenoids, terpenes, polypropanoids, lactones and glycosides. However, well-designed clinical trials are consequently required to investigate potential protective effect and therapeutic benefits of these phytochemicals against schizophrenia.